Kenaratifan Novel Haniyah dan Ala di Rumah Teteruga Karya Erni Aladjai: Kajian Naratologi H.P. Abbot - Rozekki Rozekki; Muhri Muhri (Universitas Muhammadiyah Jember, 2026)
This research aims to reveal the narrative components in the novels Haniyah dan Ala di Rumah Teteruga, namely narrative as an inherent or extensional component, a scalar or intentional component, a variable based on narrative type, and a mode among various modes. This research is included in qualitative research. Research data taken from the novel Haniyah dan Ala in Rumah Teteruga. The data is texts containing words, sentences, and paragraphs appropriate to the research problem. Data collection using library research. Data analysis uses descriptive analysis methods. The research results show that the novel has a whole narrative aspect. This is demonstrated by an inherent narrative, which shows cultural strength. Intentional narrative is indicated by the novel's sequentiality, eventfulness, reliability, and narrative competence. In variables based on narrative type, this novel shows a romantic, mystical style, but the dominant style is realist. Meanwhile, the novel genre includes historical novels. This novel is intense in portraiture mode, which reveals the story gradually.